The berth allocation problem with stochastic vessel handling times - Karafa, Jeffery; Golias, Mihalis; Ivey, Stephanie; Saharidis, Georgios K.D.; Leonardos, Nikolaos (My University, 2013)
In this paper, the berth allocation problem with stochastic vessel handling times is formulated as a bi-objective problem. To solve the resulting problem, an evolutionary algorithm-based heuristic and a simulation-based Pareto front pruning algorithm is proposed. Computational examples show that the proposed approach provides solutions superior to the ones where the expected value of the vessel handling times is used. © 2012 Springer-Verlag London Limited.
Keywords: Berth allocation; Stochastic; Optimization; Simulation